CUSTOMERS' RESPONSES TO CAUSE-RELATED MARKETING COMMUNICATIONS – A STUDY ON INFLUENCE OF VALUE ORIENTATIONS (International Journal of Food and Nutritional Sciences, 2022)
This study investigates the influence of value orientations on customers' responses to cause-related marketing communications. Cause-related marketing (CRM) is a strategic approach used by companies to promote their products or services by aligning with social or environmental causes. The aim of this research is to understand how customers' value orientations affect their attitudes and behaviors towards CRM communications.